2021
DOI: 10.1177/08982643211049079
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Decisional Determinants of Physical Activity Among Older Adults: An Integrated Behavior Approach

Abstract: Objectives The present study applied the Integrated Behavior Change Model to investigate how behavioral decisions are predicted, namely, intention, planning, and habits, with respect to physical activity. Methods: Participants were older adults (ages 65+) residing in the U.S. ( N = 667) who completed online measures of behavioral determinants (autonomous motivation, perceived behavioral control, subjective norms, attitudes, intention, habit, and consistency), in addition to past behavior. Results: A structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…Although a large variety of BCTs were integrated to promote activation factors, our findings show that for each activation factor, only a limited number of BCTs from Michie et al [11] and Dugas et al [12] were exploited. Preissner et al [45] highlighted the relevance of multiple behavioral determinants (ie, social cognitive, habitual, automatic, postintentional, and planning processes) to physical activity intention in older adults. Additionally, adult users themselves have identified a variety of BCTs to fulfill their needs and preferences for engagement with physical activity apps [46].…”
Section: Delivering Activation Factorsmentioning
confidence: 99%
“…Although a large variety of BCTs were integrated to promote activation factors, our findings show that for each activation factor, only a limited number of BCTs from Michie et al [11] and Dugas et al [12] were exploited. Preissner et al [45] highlighted the relevance of multiple behavioral determinants (ie, social cognitive, habitual, automatic, postintentional, and planning processes) to physical activity intention in older adults. Additionally, adult users themselves have identified a variety of BCTs to fulfill their needs and preferences for engagement with physical activity apps [46].…”
Section: Delivering Activation Factorsmentioning
confidence: 99%
“…The present study received ethical approval by the institutional Research Ethics Board at McGill University (#350-0119) as part of a larger survey study to examine psychosocial determinants of PA in older adults ( Kaushal et al, 2021 ; Preissner et al, 2021 ). The data to reproduce the present analyses are openly available in Mendeley Data ( http://dx.doi.org/10.17632/nvy6hpy5nk.1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Third, FoF was explicitly linked to threat appraisal to examine the direct effects of the perceived vulnerability to and the severity of falling on a person’s FoF and the subsequent effects of this pathway on PA intention. Lastly, acknowledging the contemporary gap between intention and behavior ( Sheeran & Webb, 2016 ), we included past PA performance in the model as individuals may likely differ in cognitive and motivational variables based on their PA habits; previous research has demonstrated the importance of such habituation for social cognitions as well as the intention and health behavior in older adults ( Kaushal et al, 2021 ; Preissner et al, 2021 ).…”
Section: Theoretical Basis Of Fof and Activity Behaviormentioning
confidence: 99%
See 1 more Smart Citation